Modulation of intestinal IL-37 expression and its impact on the epithelial innate immune response and barrier integrity - Kröhn, Laura; Azabdaftari, Aline; Heuberger, Julian; Hudert, Christian; Zilbauer, Matthias; Breiderhoff, Tilman; Bufler, Philip (Frontiers in Immunology, 2023)
Intestinal epithelial cells separate the luminal flora from lamina propria immune cells and regulate innate immune responses of the gut. An imbalance of the mucosal immune response and a disrupted intestinal barrier integrity contribute to the evolution of inflammatory bowel diseases. Interleukin (IL-) 37 has broad anti-inflammatory activity and is expressed by the human intestinal epithelium.Mice ectopically expressing human IL-37 show reduced epithelial damage and inflammation after DSS-induced colitis. Here, we investigated the impact of IL-37 on the innate immune response and tight junction protein expression of mouse intestinal organoids and the modulation of IL37 expression in human intestinal organoids. Expression of transgene IL-37 or recombinant IL-37Transgene IL-37 in intestinal organoids 2 protein did not significantly reduce overall proinflammatory cytokine mRNA expression in murine intestinal organoids. However, higher IL37 expression correlated with a reduced proinflammatory cytokine response in murine colonic organoids. IL37 mRNA expression in human ileal organoids was modulated by proinflammatory cytokines showing an increased expression upon TNF-α and decreased expression upon IFN-gamma stimulation. Transgene IL-37 expression did not rescue TNFα-induced changes in morphology as well as ZO-1, occludin, claudin-2 and E-cadherin expression pattern of murine jejunal organoids. We speculate that the anti-inflammatory activity of IL-37 in the intestine is mainly mediated by lamina propria immune cells protecting intestinal epithelial integrity.